BIOACCUMULATION DE LA POLLUTION PLOMBIQUE D’ORIGINE ROUTIERE AU MOYEN D’UNE MOUSSE (BRYUM ARGENTEUM) DANS LA VILLE DE TIARET (ALGERIE) : CLASSES DE POLLUTION ET CARTOGRAPHIE. - Omar Yamina; Maatoug M’hamed; Ayad Nadera; Hachemi Amine; Amirat Mokhtar (European Scientific Journal, ESJ, 2015)
The mosses are widely used as sentinels of the lead pollution from road traffic, for their morphological and physiological properties (the absence of root system and tissue developed conductors). Indeed, the mosses are used to estimate concentrations of lead emitted by vehicles in the atmosphere of the city of Tiaret (west Algeria); such was the object of this research. Mosse Bryum argenteum is used in this study, as a bio-monitor passive of trace element which is emitted by road traffic. The results show that the city of Tiaret is polluted, because the lead levels (Pb) in Bryum argenteum are considerably high (584 µg/g).